2014
DOI: 10.1186/1756-3305-7-195
|View full text |Cite
|
Sign up to set email alerts
|

Survival and swimming behavior of insecticide-exposed larvae and pupae of the yellow fever mosquito Aedes aegypti

Abstract: BackgroundThe yellow fever mosquito Aedes aegypti is essentially a container-inhabiting species that is closely associated with urban areas. This species is a vector of human pathogens, including dengue and yellow fever viruses, and its control is of paramount importance for disease prevention. Insecticide use against mosquito juvenile stages (i.e. larvae and pupae) is growing in importance, particularly due to the ever-growing problems of resistance to adult-targeted insecticides and human safety concerns reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 40 publications
5
32
0
8
Order By: Relevance
“…The susceptibility of aquatic insects to insecticides is related to physiological and behavioral constraints associated with aquatic ecosystems . In the present study we demonstrated that 2 phylogenetically related backswimmer species ( B. tarsalis and M. bentoi ) had different susceptibilities to deltamethrin, which also had effects on individual swimming activities.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The susceptibility of aquatic insects to insecticides is related to physiological and behavioral constraints associated with aquatic ecosystems . In the present study we demonstrated that 2 phylogenetically related backswimmer species ( B. tarsalis and M. bentoi ) had different susceptibilities to deltamethrin, which also had effects on individual swimming activities.…”
Section: Discussionsupporting
confidence: 48%
“…A common deltamethrin‐mediated behavioral impairment in arthropods is a decrease in locomotor activity , with consequent severe reductions in feeding and antipredator activities that lead to changes in survival (avoiding predators) or reproductive success . In the present study, short‐term exposure to deltamethrin was sufficient to alter individual (but not group) swimming activities (e.g., natural pattern of occupancy in the water column and resting time) in B. tarsalis , but not in M. bentoi .…”
Section: Discussionmentioning
confidence: 53%
“…However, little information is available about its effects on St. aegypti (Antonio-Arreola et al, 2011). Although imidacloprid has low activity against larvae and pupae compared with other insecticides, its sub-lethal effects may be important in reducing populations of St. aegypti (Tomé et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Perturbed acetylcholinesterase (AChE) activity linked to larval lethality Transient exposure of mosquito larvae to ZCE and its bioactive fraction for <5 h exhibited no obvious morphological aberrations but drastically reduced larval swimming behavior, induced muscle paralysis and immobilization leading to death. These observations are closely linked to neuromuscular toxicity effects reported by Tomé et al [45]. To ascertain whether the observed acute toxicity on mosquito larvae was as a result of suppressive effects of ZCE and its bioactive fraction on AChE, we performed the biochemical colorimetric Ellman's enzymatic assay and RT-qPCR gene expression analysis.…”
Section: Phytochemical Analysis Identi Ed An Abundance Of Insect Growmentioning
confidence: 78%